A NEW USER-FRIENDLY TEXTBOOK ON CLASSIFIERS FOR LEARNERS OF FUNDAMENTAL JAPANESE - Srikittiwanna, Kitpakorn; Na Ranong, Soysuda (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2024)
The objectives of this research were as follows: 1. To develop a classifier textbook for elementary Japanese learners, and 2. To study the opinions of elementary Japanese learners towards the activities and exercises created by the researcher. The sample group consisted of students enrolled in a Japanese language program. The participants were 40 students in the 4th grade at Thep-Leela School, divided into two groups: a control group comprising 20 students and an experimental group comprising 20 students. The data collection tools were a classifier textbook for elementary Japanese learners, a test on the use of classifiers for elementary Japanese language learners, and a student satisfaction questionnaire. The data analysis included calculating percentage, the mean, standard deviation, and Dependent t-test. The research found that the average score of the post-test on the use of classifiers for elementary Japanese language learners indicated that the experimental group's score was significantly higher than the control group's average score, at the 0.05 significance level. Regarding the opinions of elementary Japanese language learners towards the activities and textbooks created by the researcher, it was evident that overall satisfaction was at the highest level.